Shoot and plantlet regeneration from meristems of Dioscorea rotundata poir and Dioscorea alata L. - Adeniyi, O.J.; Adetimirin, Victor O.; Ingelbrecht, I.L.; Asiedu, Robert (2008)
In vitro culture media capable of regenerating moderate to high shoots and/or plantlets from meristems of two yam species – Dioscorea rotundata and Dioscorea alata within comparable duration of 10 weeks as commonly obtained in other monocots and root and tuber crops were investigated. The study comprised 125 phytohormone combinations investigated in three factorial experiments each consisting of an auxin (NAA) and a cytokinin (BAP or kinetin), or two cytokinins only. The frequency of direct plantlet regeneration, though significantly (P < 0.05) higher for D. alata than for D. rotundata, was low and ranged from 0 to 10% at 3 weeks after culture (WAC) and 0 to 35% at 8 WAC. At 8 WAC, shoot regeneration of 42-75% was obtained in D. rotundata in MS medium supplemented with 0.1 M NAA + 0.20 M BAP, and shoot + plantlet regeneration of 60-82% obtained in media containing 0.05 M + 0.20 M BAP or 0.46 M BAP + 0.50 M kinetin in D. alata. Both shoot induction and plantlet regeneration were species-dependent. Induced shoots were successfully rooted in MS medium within 3 to 4 weeks, bringing time taken for plantlet regeneration to 11 to 12 weeks. Regenerants were morphologically similar to the mother plants. Results of the present study will facilitate regeneration of plantlets via meristem in D. rotundata and D. alata.